2016
DOI: 10.1016/j.bspc.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Collaborative Representation based Classification for hand gestures recognition on electromyography signals

Abstract: a b s t r a c tThe classification of the bio-signal has been used for various purposes in the literature as they are versatile in diagnosis of anomalies, improvement of overall health and sport performance and creating intuitive human computer interfaces. However, automatic identification of the signal patterns on a streaming real-time signal requires a series of complex procedures. A plethora of heuristic methods, such as neural networks and fuzzy systems, have been proposed as a solution. These methods stipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 33 publications
0
23
0
4
Order By: Relevance
“…The signal from the hardware is transmitted wirelessly to a computer using the Bluetooth Low Energy (BLE) protocol. This system provides a good research platform and has now been used in different studies [36][37][38]. In each experimental session, subjects were first guided about the experimental protocol and they were asked to produce a medium level contraction from rest to motion, prompted by the image of the selected motion using a custom-made Graphical User Interface (Figure 1b).…”
Section: A) Subjectsmentioning
confidence: 99%
“…The signal from the hardware is transmitted wirelessly to a computer using the Bluetooth Low Energy (BLE) protocol. This system provides a good research platform and has now been used in different studies [36][37][38]. In each experimental session, subjects were first guided about the experimental protocol and they were asked to produce a medium level contraction from rest to motion, prompted by the image of the selected motion using a custom-made Graphical User Interface (Figure 1b).…”
Section: A) Subjectsmentioning
confidence: 99%
“…Matos et al [ 76 ] identified leg gestures with the Myo sensor (see Section 2.2 ) by division of gestures into five moments and a ranking approach to provide a HCI solution for upper limb amputees. Boyali et al [ 159 ] use the Myo sensor to detect the eight Myo hand gestures (s. Section 2.2 ). Spectral Collaborative Representation based Classification (CRC) using the Eigenvalues of observed signals as features is used for gesture recognition with an accuracy of more than 97.3%.…”
Section: Methodsmentioning
confidence: 99%
“…Given n k training samples from k-th class as columns of a matrix But the problem of finding the solution of l 0 -norm is NP-hard, so approximate solutions are adopted generally. Algorithms of research include: greedy algorithm, including matching tracking algorithm, orthogonal matching pursuit algorithm, etc., to realise signal approximation through choosing appropriate atoms and a series of progressively increasing method (Boyali and Hashimoto, 2016). Convex optimisation algorithm, including gradient projection method, tracking methods the minimum point of regression method, etc., put the l 0 -norm relax to l 1 -norm by solving linear programming (Khan and Raja, 2016).…”
Section: Sparse Representation Theorymentioning
confidence: 99%